Intellectual disability in the English teaching and learning process - Guanín Chasi, Lissette Estefanía (2023)
Throughout the years, the educational system has gone through several changes, giving children the right to be part of the educational system. That is, within the teaching and learning process of the English language, children with different needs can be included, as well as children with intellectual disabilities. The main objective of this research project was to analyze the opinions about the teaching and learning process in a classroom with children with intellectual disabilities (ID) of the Eloy Alfaro Educational Unit during the 2022-2023 school year. A qualitative descriptive methodology was used. In addition, to achieve the research objective, data were collected through semi-structured interviews with the English teacher, the child with intellectual disabilities and the mother. Thematic analysis was used to analyze the data obtained. The main findings within this study yielded different opinions about the English language teaching-learning process in children with Intellectual Disability (ID); obtaining results about the opinions about the English teaching process in children with ID, categories were presented that make known the learning strategies with the contents related to the student's environment. In addition, the use of specific material for the student with ID as a didactic resource was known, which is adapted to the same content, but at a different level as a type of curricular adaptation, which leads to understand that personalized education allows the student to develop at his own pace and finally the lack of knowledge as an English teacher in children becomes a challenge when teaching. On the other hand, the research findings about intellectual disability in students learning progress show that the student is achieving significant learning at the basic levels in the language. In the same way the difficulty in pronunciation, and the deficiency in writing become limitations of ID students. Consequently, the mother despairs because her daughter does not manage on her own, which is a family challenge. While the desire to learn constantly reflects a good attitude and motivation. Finally, it is identified that the mother's sentimental support and her sister's frequent help are usually the main family support for the girl to develop in an inclusive environment.